EFFECT OF BACTERIAL VOLATILE COMPOUNDS ON PAKCOY (Brassica rapa L.) GROWTH PROMOTION - Phabiola, Trisna Agung; Khalimi, Khamdan; Wiguna, Putu Perdana Kusuma (International Journal of Biosciences and Biotechnology, 2022)
This research was aimed to test of the ability of MVOC-producing bacteria to increase plant growth of Pakcoy ( Brassica rapa L .). The methodology including testing the ability of MVOC-producing rhizobacteria in Pakcoy plant growth enhancement, MVOC extraction and analysis of compounds in MVOC Extracts using Gas Chromatography. Different bacterial species produce different MVOC . S. maltophilia Sg3 emitted 20 MVOC compounds and MVOC that contribute to increasing plant growth, namely oxalic acid, cyclohexyl undecyl ester, 2-Furancarboxaldehyde, 5-methyl-, 1,2 butanediol, and Piperazine. E. asburiae MjSg48 emitted 12 MVOC compounds and those that contributed to increasing plant growth were oxalic acid, cyclohexyl dodecyl ester and 4-methyl oxazole. E. asburiae TK24 emitted 27 MVOC compounds and those that contributed to increasing plant growth were oxalic acid, isohexyl neopentyl ester, thiazole, Oxalic acid, and cyclohexyl decyl ester. Meanwhile P. rettgeri Al2TT emitted 13 MVOC compounds and those that contributed to increasing plant growth were oxalic acid, diisohexyl ester, and Pyridine, 2,3,4,5-tetrahydro.